Disaster Situation and Humanitarian Emergency – In-Between Responses to the Refugee Crisis in Germany - Cordula Dittmer; Daniel F. Lorenz (International Migration, 2021)
In 2015, the needs of hundreds of thousands of refugees who arrived in Germany could only be met by deploying all available civil protection units. This article presents procedures and practices of state and non-state formal actors in the field of civil protection and related crisis management structures implemented and established across the board in the municipalities, the Federal Government and mass shelters, in particular in Bavaria. From a disaster research and humanitarian studies perspective we use the concept of “patterns of interpretation” to analyse the application of the “humanitarian emergency” and the “disaster situation” procedures to discuss whether the situation can really be categorized as “either-or” or whether the coexistence of the two served a function in managing such a complex situation. Finally, we discuss some developments that occurred after 2015/16 and consider the extent to which these developments shift or expand the existing patterns of interpretation.
Keywords: 300